A common 8q24 variant in prostate and breast cancer from a large nested case-control study. - Schumacher, F; Feigelson, H; Cox, D; Haiman, C; Albanes, D; Buring, J; Calle, E; Chanock, S; Colditz, G; Diver, W; Dunning, A; Freedman, M; et al. (2007)
Two recent studies independently identified polymorphisms in the 8q24 region, including a single nucleotide polymorphism (rs1447295), strongly associated with prostate cancer risk. Here, we replicate the overall association in a large nested case-control study from the National Cancer Institute Breast and Prostate Cancer Cohort Consortium using 6,637 prostate cancer cases and 7,361 matched controls. We also examine whether this polymorphism is associated with breast cancer among 2,604 Caucasian breast cancer cases and 3,118 matched controls. The rs1447295 marker was strongly associated with prostate cancer among Caucasians (P = 1.23 x 10(-13)). When we exclude the Multiethnic Cohort samples, previously reported by Freedman et al., the association remains highly significant (P = 8.64 x 10(-13)). Compared with wild-type homozygotes, carriers with one copy of the minor allele had an OR(AC) = 1.34 (99% confidence intervals, 1.19-1.50) and carriers with two copies of the minor allele had an OR(AA) = 1.86 (99% confidence intervals, 1.30-2.67). Among African Americans, the genotype association was statistically significant in men diagnosed with prostate cancer at an early age (P = 0.011) and nonsignificant for those diagnosed at a later age (P = 0.924). This difference in risk by age at diagnosis was not present among Caucasians. We found no statistically significant difference in risk when tumors were classified by Gleason score, stage, or mortality. We found no association between rs1447295 and breast cancer risk (P = 0.590). Although the gene responsible has yet to be identified, the validation of this marker in this large sample of prostate cancer cases leaves little room for the possibility of a false-positive result.